Relational Social Theories and Legal Pluralism - Benda-Beckman, Keebet von (The Indonesian Journal of Socio-Legal Studies, 2021)
Recent sociological, anthropological, and psychological research points at a shared problem: Are humans separate and autonomous entities, or must they be seen through the lens of extended, permeable, fractured notions of personhood? This paper discusses some crucial implications for the study of law and legal pluralism. Legal orders may differ in the degrees to which personhood is taken as embedded. At the same time, notions of personhood may also be more or less bounded, with particular fields within legal orders also espousing different degrees of personal autonomy. That depends on how political preferences shape specific issues at the time legislation is enacted. All this has implications for conceptualizing and studying legal pluralism. Examples from Indonesia, Thailand, and the Netherlands bring to light some thorny issues that arise when personhood is viewed through the lens of more or less autonomy and social embeddedness. The examples suggest that a relational approach that accounts for varying degrees to which persons are perceived as extended beings deepens the analysis of plural legal orders.